2005
DOI: 10.1109/tnsre.2004.841384
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the stationarity of paediatric aspiration signals

Abstract: Abstract-An aspiration signal is the time-varying anterior-posterior acceleration measured infero-anterior to the thyroid notch when foreign material enters the airway during inspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
1
42
0
5
Order By: Relevance
“…The RAT is often used to evaluate the weak stationarity of physiological and biomedical signals (Alves and Chau, 2008;Chau et al, 2005;Nhan and Chau, 2009;Harris et al, 1993;Hampson et al, 2005;Bilodeau et al, 1997;Novak et al, 1996).…”
Section: Reverse Arrangements Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAT is often used to evaluate the weak stationarity of physiological and biomedical signals (Alves and Chau, 2008;Chau et al, 2005;Nhan and Chau, 2009;Harris et al, 1993;Hampson et al, 2005;Bilodeau et al, 1997;Novak et al, 1996).…”
Section: Reverse Arrangements Testmentioning
confidence: 99%
“…The minimum window size was constrained to include at least 10 stride intervals and the maximum window size was constrained to include at least 10 windows (for all series but one). In this way, we maintained an adequate number of data points as required to estimate a single statistical parameter (Chau et al, 2005) when calculating both the mean squared value within each interval and the total number of reverse arrangements.…”
Section: Stationarity Testingmentioning
confidence: 99%
“…We have employed the Bendat and Piersol's runs test, a general non-parametric test for weak or wide sense stationarity [12]. The assessment of stationarity with this method depends on the window size, which can be determined by roughly estimating the dominant low frequency band in terms of energy distribution [13]. We found that over half of the MEG epochs retained the majority of their energy below 10.6 Hz.…”
Section: Stationaritymentioning
confidence: 99%
“…Thus, a window of at least 94.3 ms is necessary. As a conservative estimate, the windows size should be more than three times the previous value [13]. Thus, in our study, a window length of 300 ms, that is 50 samples, was employed to test the stationarity.…”
Section: Stationaritymentioning
confidence: 99%
“…Essas variáveis se referem à potência e variância. Destas variáveis estudadas, somente duas estão presentes em trabalhos sobre disfagia, que são estacionaridade e taxa de dispersão (LEE et al, 2006a;CHAU et al, 2005).…”
Section: Classificadoresunclassified